2019
DOI: 10.1039/c9nr07416c
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the positive roles of liquid polysulfides in alkali metal–sulfur electrochemistry: from electrolyte additives to active catholyte

Abstract: The positive roles of dissolved polysulfides in Li–S electrochemistry are discussed, followed by a progress summary of alkali metal-polysulfide (redox flow) batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 162 publications
0
4
0
Order By: Relevance
“…7 However, it was shown that some reactions between lithium polysulfide species and Li metal anodes can enhance passivation and effectively suppress the growth of Li dendrites and to increase the Coulombic efficiency of the process of Li plating/stripping on stainless steel or copper substrates. [8][9][10] In this work we present the results of the study of the cycling behavior of Li metal anodes with practical cycling parameters with both Li|Li symmetric and full Li-S cells with binder free composite S/carbon electrodes. We demonstrate the effect of the initial presence of LPS in the electrolyte solution (as an additive) on the increased cycling stability and efficiency of the cells.…”
mentioning
confidence: 99%
“…7 However, it was shown that some reactions between lithium polysulfide species and Li metal anodes can enhance passivation and effectively suppress the growth of Li dendrites and to increase the Coulombic efficiency of the process of Li plating/stripping on stainless steel or copper substrates. [8][9][10] In this work we present the results of the study of the cycling behavior of Li metal anodes with practical cycling parameters with both Li|Li symmetric and full Li-S cells with binder free composite S/carbon electrodes. We demonstrate the effect of the initial presence of LPS in the electrolyte solution (as an additive) on the increased cycling stability and efficiency of the cells.…”
mentioning
confidence: 99%
“…A monolayered polypropylene separator (Celgard 2500) was placed between the cathode and the anode. A PS (Li 2 S 6 ) catholyte was prepared for loading into the conductive hosts of CF and C porous @CF. , A mixture of 0.5 M Li 2 S (99.9%, Alfa Aesar) and 2.5 M Sulfur (99%, Showa, Japan) was dissolved in an electrolyte solution containing lithium bis­(trifluoromethanesulfonyl)­imide (LITFSI; 99%, Acros) and lithium nitrate anhydrous (LiNO 3 ; 99%, Alfa, U.K.) (0.5 M each) in a cosolvent of 1,3-dioxolane (DOL, Alfa Aesar) and dimethoxyethane (DME, Alfa Aesar) (1:1 w/w) at 50 °C. The catholyte concentration prepared above was equivalent to an areal S loading of 4.3 mg cm –2 in the cathode.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting CF with an additional porous carbon structure was imaged using scanning electron microscopy (SEM). For applications, we tested the modified CF as the cathode host for Li–polysulfide (Li–PS) batteries. The electrochemical performance was assessed by capacity and rate capability measurements, cyclic voltammetry (CV), and electrochemical impedance spectroscopy (EIS). The diffusion coefficient of Li + was determined using CV analysis and the galvanostatic intermittent titration technique (GITT).…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Indeed, it was show that some reactions between lithium polysulfide species and Li metal anodes can enhance passivation and effectively suppress the growth of Li dendrites and to increase the Coulombic efficiency of the process of Li plating/stripping on stainless steel or copper substrates. [14][15][16][17] According to Ref. 14, a stable and uniform solid electrolyte interphase layer is formed due to a synergetic effect of both LPS and LiNO 3 as additives in etherbased electrolyte solutions.…”
mentioning
confidence: 99%